2022
DOI: 10.1002/ajp.23390
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and molecular analyses of the deltoid muscle in chimpanzees (Pan troglodytes) and modern humans (Homo sapiens): Similarities and differences due to the uses of the upper extremity

Abstract: In the deltoid muscles of Pan troglodytes and Homo sapiens, we have analyzed the muscle architecture and the expression of the myosin heavy chain (MHC) isoforms.Our aim was to identify differences between the two species that could be related to their different uses of the upper limb. The deltoid muscle of six adult Pan troglodytes and six adult Homo sapiens were dissected. The muscle fascicle length (MFL) and the physiological cross-sectional area (PCSA) of each muscle were calculated in absolute and normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(182 reference statements)
0
1
0
Order By: Relevance
“…Musculus acromiodeltoideus or the m. deltoideus pars acromialis is the main abductor muscle for the arm, supported by the m. supraspinatus (Argot 2001). In some primates, elevating and stabilizing functions of the deltoid muscles is important for arboreal locomotion (Gómez et al 2022) and it is suggested that the deltoid muscles in the large flying fox share similar functional characteristic to support active flying activity. Musculus infraspinatus that fills the fossa infraspinata, has the opposite function to m. supraspinatus, since it acts as a flexor of the humerus, although synergistically it makes the wing abduction movements (Norberg 1972).…”
Section: Back Pectoral Shoulders and Arms Musclesmentioning
confidence: 99%
“…Musculus acromiodeltoideus or the m. deltoideus pars acromialis is the main abductor muscle for the arm, supported by the m. supraspinatus (Argot 2001). In some primates, elevating and stabilizing functions of the deltoid muscles is important for arboreal locomotion (Gómez et al 2022) and it is suggested that the deltoid muscles in the large flying fox share similar functional characteristic to support active flying activity. Musculus infraspinatus that fills the fossa infraspinata, has the opposite function to m. supraspinatus, since it acts as a flexor of the humerus, although synergistically it makes the wing abduction movements (Norberg 1972).…”
Section: Back Pectoral Shoulders and Arms Musclesmentioning
confidence: 99%